Prevalence of agenesis of palmaris longus in male and female genders on clinical examination – a review - Quratulain Javaid (Journal of the Pakistan Medical Association, 2022)
Palmaris longus is a muscle that is located in the anterior compartment of the forearm. Among the muscles belonging to the flexor compartment of forearm, palmaris longus is located at the most superficial position and that is why it is easy to access. It exhibits high variability and its prevalence ranges between 1.5% and 63.9%. The knowledge of prevalence of agenesis of palmaris longus is essential both in terms of updating anatomical information and also for physicians, radiologists, physiotherapists and surgeons. The surgeons must know about the variability as it may be beneficial while they plan surgeries involving the palmaris muscle as a graft. The current narrative review was planned to highlight the variability pattern of palmaris longus muscle in terms of prevalence, gender and laterality. Palmaris longus agenesis is more common in females and on the left side. Besides, unilateral agenesis is more common compared to bilateral agenesis. Continue...